Pengembangan Instrumen Test Diagnostik Multiple Choice Four Tier Pada Materi Ikatan Kimia - Pangoloan Soleman Ritonga; Arif - Yasthophi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The purpose of this study was to design and develop diagnostic test for analysis of student misconception in chemical bonding materials. Diagnostic that we develop in this study was four-tier diagnostic test. the diagnostic test consisted of 25 questions which cover 20 indicator in chemical bonding materials. From the test result obtained the higest was in a determine the bonding that consist in the compound (39,45%) and the lowest misconception was in a interpret the process in chemical bonding formation process (1,83).